The Mammoth Academy in trouble! - Layton, Neal (Henry Holt and Co., 2009)
As Mammoth Academy spends a term excitedly preparing for its Founder's Fiesta, wild and dangerous animals called humans are spraying the school's gates with graffiti and threatening the students.